Pengaruh Inovasi Produk dan Brand Trust Terhadap Keputusan Pembelian Produk Infinix di Kota Bima - Rahim, A; Ernawati, Sri; Hamidah, Nur Khusnul (NAAFI: JURNAL ILMIAH MAHASISWA, 2025)
This study aims to analyze the effect of product innovation and brand trust on the purchasing decision of Infinix products in the city of Bima, both partially and simultaneously. The background of this study arises from the phenomenon of increasing demand for high-quality smartphones at affordable prices, as well as the importance of innovation and brand trust in influencing consumer behavior. The research method used is an associative quantitative method with a survey approach. Data was collected through a Likert-scale questionnaire from 96 respondents selected using purposive sampling technique. Data analysis was performed using validity tests, reliability tests, classical assumption tests, multiple linear regression analysis, as well as t-tests and F-tests using SPSS version 26. The results show that the product innovation variable does not have a significant effect, while brand trust has a significant effect on purchasing decisions. Simultaneously, both variables significantly influence consumer purchasing decisions. This finding emphasizes the importance of building brand trust in Infinix's marketing strategy, while product innovation needs to be directed towards aspects that are more relevant to the needs of local consumers.